Business Consulting Improving of cash flow through the implementation of the inventory consignment model for a company in the hydrocarbons sector - Rodriguez Diaz, Giannina Gladys (2024)
The hydrocarbon (lubricants) sector is characterized by high levels of investment in fixed assets, volatility in raw material prices, and the need to manage large volumes of inventories, which directly impacts working capital and cash flow. In this context, many companies face difficulties in maintaining a balance between ensuring inventory supply and not tying up large amounts of capital that could be better used in other strategic areas. This thesis proposes the implementation of an inventory consignment model as a strategic solution to improve working capital management and optimize cash flow in a hydrocarbon company. Under this model, suppliers retain ownership of the products until they are used or sold, which allows the company to significantly reduce the amount of capital tied up in inventories, thus freeing up resources for other uses. The study includes a comparative evaluation of the inventory consignment model that is already used by companies in other industrial sectors, such as Gloria, Alicorp, and San Miguel Industries. These companies have successfully implemented this model, reducing warehousing costs, improving operational efficiency, and optimizing their cash conversion cycle. In order to evaluate the feasibility of implementing the consignment model in the company that is the subject of this study, qualitative and quantitative analysis tools were used. Interviews were conducted with the heads of key areas such as production, finance, marketing, and logistics, as well as visits to the plant facilities to understand the current inventory flows. The implementation of the inventory consignment model in the hydrocarbon company is expected to generate the following key results: Reduction of capital tied up in inventories, which will improve the company's liquidity. Optimization of cash flow by reducing the need for large cash outlays before products are used or sold. Improved operational efficiency by having more efficient inventory control, which will reduce storage and handling costs. Greater flexibility in inventory management, allowing the company to better adapt to changes in demand or market conditions. In conclusion, we can say that the inventory consignment model represents a key opportunity to improve working capital management in the hydrocarbon company, aligning itself with the best practices of leading companies in the industrial sector. By applying this model, the company will be able to optimize its cash flow, reduce operating costs and improve its ability to respond to market fluctuations, thus improving its long-term competitiveness. As well, the Company will be able to extrapolate this model to other operating units, in order to increase margins and profitability to consider options in an investment portfolio.